Assessing the urgency and feasibility of wealth tax implementation in Indonesia - Putri, Ayudya Purwani; Marfiana, Andri (WIM Solusi Prima, 2025)
The growing economic inequality in Indonesia necessitates the adoption of fairer fiscal policies, including the implementation of a wealth tax. This study employs a qualitative case study approach to assess the potential of wealth taxation targeting High Net Worth Individuals (HNWIs). Data were obtained through comparative analysis of international wealth tax policies and interviews with government officials, academics, and tax practitioners. The findings reveal that a wealth tax could function as an effective instrument for economic redistribution, yet its implementation faces challenges such as resistance from affluent groups, risks of capital flight, and asset valuation complexities. Evidence from Switzerland, Japan, and Bolivia highlights that successful implementation depends on sound policy design, including appropriate wealth thresholds, progressive rates, and strong enforcement mechanisms. To ensure effectiveness in Indonesia, strategic measures involving regulatory clarity, administrative capacity building, and international cooperation are essential. A well-structured wealth tax may increase state revenue while reducing economic disparity sustainably. Keywords: Economic Inequality; High Net-Worth Individuals; Wealth Redistribution; Wealth Tax.